Arthropod abundance modulates bird community responses to urbanization. Issue 1 (2nd October 2020) - Planillo, Aimara; Kramer‐Schadt, Stephanie; Buchholz, Sascha; Gras, Pierre; von der Lippe, Moritz; Radchuk, Viktoriia
Abstract: Aim: We analysed the role of species interactions in wildlife community responses to urbanization. Specifically, we investigated non‐trophic associations within a bird community and the role of trophic interactions in the responses of bird species to the urbanization gradient. Location: City‐state of Berlin, Central Europe. Methods: Arthropod and bird abundances were sampled across the study area and analysed using hierarchical joint species distribution models (JSDMs). Urbanization gradient was defined by environmental predictors reflecting anthropogenic disturbances, for example noise level and human population density, as well as nature‐like features, for example tree cover and open green area. Relevant environmental predictors for each group and relevant spatial resolution were selected a priori using AICc. Arthropod abundances were modelled for the bird sampling transects and included as additional predictor variable in the bird community model. In this model, we used abundances and traits of 66 breeding bird species as response variables. Results: Bird species responses to urbanization were captured by the interaction between invertebrate abundance and environmental predictors. We identified three groups of birds: the urban group (12 species) showed no decrease in abundance along the urbanization gradient and were not related to arthropods abundance; the woodland group (18 species) were positively related to tree cover and arthropod abundance, also in areas with high anthropogenic disturbance; and the nature group (36 species) were positively related to arthropod abundance, but the species abundance decreased sharply with increasing anthropogenic disturbance. All the non‐trophic associations found within the bird community were positive. Main conclusions: Arthropod abundance clearly modulated birds' responses to the urbanization gradient for most species. Especially at moderate levels of anthropogenic disturbance, the abundance of arthropods is key for the occurrence and abundance of bird species in urban areas. To maintain bird diversity in urban green areas, management measures should focus on maintaining and increasing invertebrate abundance.